2023
DOI: 10.3390/su15043714
|View full text |Cite
|
Sign up to set email alerts
|

Megalithic Stone Heritage Trail Mapping Using GIS as Tourism Product for Cultural Sustainability in Tambunan

Abstract: Heritage trails are an effective way to preserve cultural sustainability. Nowadays, heritage trails have been widely developed as tourism products either domestically or abroad. Megalithic stones are an ancient tradition of high value that has interesting functions and backgrounds. Moderni-zation with infrastutural development, and changes in religion in society have caused the mega-lithic stone tradition to be less practiced and increasingly declining. One of the effective ways to preserve megalithic stones f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Data DEM ditakrifkan sebagai set digital tersusun atau tidak tersusun bagi ketinggian tanah (ketinggian titik) untuk perwakilan rupa bumi (Zhou, 2017). Dalam konteks visual 3D, data DEM akan berupaya memberikan gambaran rupa bentuk muka bumi sebenar di dalam bentuk digital atau kontur seperti bukit, kawasan tanah rendah dan juga dasar sungai (Sieng et al, 2023). Peranan data ini sangat-sangat besar dalam kajian ini kerana daripada data ini dapat menghasilkan perbezaan tanah tinggi dan tanah rendah.…”
Section: Data Digital Elevation Model (Dem)unclassified
“…Data DEM ditakrifkan sebagai set digital tersusun atau tidak tersusun bagi ketinggian tanah (ketinggian titik) untuk perwakilan rupa bumi (Zhou, 2017). Dalam konteks visual 3D, data DEM akan berupaya memberikan gambaran rupa bentuk muka bumi sebenar di dalam bentuk digital atau kontur seperti bukit, kawasan tanah rendah dan juga dasar sungai (Sieng et al, 2023). Peranan data ini sangat-sangat besar dalam kajian ini kerana daripada data ini dapat menghasilkan perbezaan tanah tinggi dan tanah rendah.…”
Section: Data Digital Elevation Model (Dem)unclassified
“…A recent study by Sieng et al (2023) have also identified several advantages of using GIS in tourism, namely, regarding to the mapping of the five elements that these authors identify as the most important in a tourist destination: attractions, activities, accessibility, accommodation and facilities. In their study they found that using GIS techniques and approaches can contribute positively to produce “an accurate heritage trail map” which will benefit tourists (Sieng et al, 2023, p. 4) and decision-makers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Tambunan site was recorded and megalithic stones were mapped. Then, least-cost path analysis (LCPA) in GIS was used to identify cost-effective and sloping routes to produce heritage trails [14]. An integrated GIS system for the organization and planning of two cultural routes in Chios Island, Greece based on in-situ observations and the study of the corresponding spatial and legal framework is presented in [15].…”
Section: Literature Reviewmentioning
confidence: 99%